A three-year experience with medial-pedicle-based breast reduction for different mammary hypertrophy - Grieco, Michele Pio; Bertozzi, Nicolò; Grignaffini, Eugenio; Raposio, Edoardo (Acta Biomedica Atenei Parmensis, 2018)
Background and aim: The aim of breast reduction is to reduce excessive breast volume, ensuring an adequate vascular supply and sensitivity of the nipple-areola complex, as well as to produce an aesthetically pleasing final shape. The authors report on their experience with medial-pedicle-based breast reduction combined with both vertical and inverted-T skin resection patterns for different types of breast hypertrophy. Methods: From January 2012 to June 2015, 27 female patients (mean age: 49 years) underwent reduction mammoplasty with the medial pedicle technique. The choices of medial pedicle base widths were: 6 cm for low-grade mammary hypertrophy (350-500 gr per breast), 6-8 cm for medium-grade hypertrophy (500-1000 gr per breast), or 8-10 cm for severe mammary hypertrophy (>1000 gr per breast). The authors chose the model of vertical skin resection for low-grade breast hypertrophy. The vertical model was used for medium-grade breast hypertrophy, and Wise skin resection was chosen on a case-by-case basis; only the Wise model was applied to severe breast hypertrophy. Results: The mean weight of breast excised was 540 g on the left (range, 207 to 1160 g) and 564.8 g on the right (range, 215 to 1150 g). The complications were minor and self-limiting. All patients reported relief of neck pain, back pain, and bra strap indentations after 6 months of follow-up. Conclusions: Breast reduction surgery must address both functional and aesthetic issue by restoring an aesthetically pleasing shape to ptotic or hypertrophic breasts, repositioning the NAC in a physiological position. Various breast reduction techniques have been attempted to combine the safety of the pedicle with aesthetic and functional results. Surgeons should tailor the best technique to each patient. We found that medial-pedicle-based reduction mammoplasty is effective and reliable because it can be applied to a wide range of breast hypertrophy, with reproducible breast weight reduction and results that are aesthetically satisfactory for both patients and surgeons.